Utility of Unenhanced CT KUB: Beyond Urolithiasis - Nida Rafiq; Binish Rasheed; Nasreen Naz; Nauman Al Qamari; Uzma Azmatullah; Anila Rahim (KARACHI MEDICAL AND DENTAL COLLEGE, 2023)
Abstract Background: Renal colic is one of the most common symptoms encountered in Emergency Departments. Unenhanced helical CT KUB has become the mainstay for diagnostic imaging of patients with suspected urinary tract stones. This superiority is due to its ability to detect renal and extra-urinary abnormalities. Objective: To determine the frequency of urinary and extra-urinary pathologies as well as audit the missed findings on CT KUB scan. Methods: We retrospectively reviewed 250 consecutive CT KUB studies requested for suspected renal colic at the Radiology department of a tertiary care hospital. A consultant radiologist reviewed the CT KUB images for calculus, non-calculus urinary pathologies, and extra urinary incidental findings and recorded them on a proforma. Another consultant reviewed the initial radiological report and tallied it for any discrepancies. Findings were recorded on the same proforma. Results: Of 250 patients, mean age of patients was 38.56 ±15.22 years. 163 (65.2%) were males while 87 (34.8%) were females. Overall positive yield for urolithiasis was 61.2%, congenital anomalies were observed in 6.2%, cyst in 2.8%, infection in 2.2%, and miscellaneous renal findings in 2.8%. Extrarenal findings were found in 32% of cases, most common hepatobiliary/spleen diseases (32.5%) followed by musculoskeletal disease in 27.5%. Discordant findings were seen in 5.2% of the cases.  Conclusion: Unenhanced CT KUB is an ideal investigation for diagnosing renal and ureteric calculi and showing alternative mimickers of renal colic. However, it should be wisely advised to avoid unnecessary ionizing radiation. Keywords: extra urinary, non-contrast-enhanced CT, renal, renal colic, urolithiasis